HEM 2022
DOI: 10.21272/hem.2022.1-07
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in Research on Confidence in the Healthcare System

Abstract: The sphere of trust in the health care system, which is actively developing in covid and postcovid conditions, is accompanied by a significant increase in the amount of scientific literature that requires detailed analysis. Accordingly, the primary purpose of this study is to conduct a multilevel bibliometric analysis of publications on trust in the health care system. This will provide a global picture of the phenomenon to determine the dynamic aspects of trends from a statistical point of view, using content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…From the demand side, population aging promotes the increase of medical expenses and promotes the demand for elderly care services [25][26][27][28][29][30][31][32]. Although Cai et al [25] confirmed that the labor participation rate of the elderly is low, the labor income effect decreases rapidly, and their consumption level will shrink with the increase of age [25], and the increasing degree of the aging of China's population.…”
Section: Literature Review 21 Population Aging and Economic Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…From the demand side, population aging promotes the increase of medical expenses and promotes the demand for elderly care services [25][26][27][28][29][30][31][32]. Although Cai et al [25] confirmed that the labor participation rate of the elderly is low, the labor income effect decreases rapidly, and their consumption level will shrink with the increase of age [25], and the increasing degree of the aging of China's population.…”
Section: Literature Review 21 Population Aging and Economic Growthmentioning
confidence: 99%
“…The inhibition of household consumption rate is increasingly significant [26]. However, these studies ignore the fact that consumption age is a key factor of consumption structure [27][28][29][30], because the elderly's consumption habits are particular. The increase of the elderly population will lead to a new consumer demand structure, although the elderly demand for fashion clothing, jewelry, and other luxuries is relatively weak.…”
Section: Literature Review 21 Population Aging and Economic Growthmentioning
confidence: 99%
“…The concept of macroeconomic stability is a complex, multifaceted category, characterized by a multilevel structure, the presence of complex multilateral relationships, complexity and certain uncertainty of functioning conditions. A significant list of objects and subjects of management significantly complicates the procedures for managing macroeconomic stability, ensuring the coherence of the functioning of its individual components, delimiting functions and powers between its institutions and, in general, reduce the effectiveness of its functioning (Kot & Paradowski, 2022;Litovseva et al, 2022;Kharazishvili & Kwilinski, 2022;Lyeonov et al, 2021a;Mendoza et al, 2022;Piecha et al, 2022;Tahat, 2023;Valaskova & Nagy, 2023;Van de Walle & Bouckaert, 2007).…”
Section: Introductionmentioning
confidence: 99%